FLOW AND FLUCTUATIONS OF PRESSURE STRUCTURE INSIDE THE OVAL HOLE - Воскобійник, В. А.; Воскобійник, А. В. (Science-based technologies, 2011)
The results of experimental researches of forming and evolution of vortex flow and intensity of the field of wallpressure fluctuations are presented inside and round the oval dimple which is located on a smooth plate inclined under the corner of 60 degrees. Experiments are conducted for the laminar regime of flow. The features of the vortex generation are certain inside the oval dimple and their break up outside in boundary layer. The distributions of root-mean-squares of the wallpressure fluctuations is got on the streamlined surface of dimple and in its environment. It is set that pressure fluctuations in lower wake of dimple almost on an order higher, than on its bottom.